Pelatihan Menggunakan Aplikasi Canva Untuk Meningkatkan Life Skill Siswa Program Paket C di PKBM Mandiri Kabupaten Lombok Utara - sa'di, Kholisus (Jurnal Dedikasi Madani, 2024)
Training using the Canva application is a strategic step by the Mandiri Center for Community Learning Activities (PKBM) in improving the quality of education and life skills of Package C Program students in North Lombok Regency. By utilizing technology and encouraging creativity, it is hoped that students can develop a variety of skills that will be beneficial for their future. This training also reflects PKBM Mandiri's commitment to providing relevant and quality education for all students. The method used is the lecture method, and the practice of creating a design using the Canva application while playing. The results of the training on the use of the Canva application organized by PKBM Mandiri North Lombok Regency succeeded in improving the life skills of Package C Program students. This training not only equips students with basic knowledge and skills in graphic design, but also enhances their creativity and visual communication abilities. Students become proficient in using Canva's features and are able to create engaging and informative visual materials for academic and personal use.